2020
DOI: 10.3390/en13174579
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of Synthetic Natural Gas Production from Different CO2 Sources: A Cradle-to-Gate Study

Abstract: Fuel production from hydrogen and carbon dioxide is considered an attractive solution as long-term storage of electric energy and as temporary storage of carbon dioxide. A large variety of CO2 sources are suitable for Carbon Capture Utilization (CCU), and the process energy intensity depends on the separation technology and, ultimately, on the CO2 concentration in the flue gas. Since the carbon capture process emits more CO2 than the expected demand for CO2 utilization, the most sustainable CO2 sources must be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
(29 reference statements)
1
7
1
Order By: Relevance
“…In comparison to the study by Bargiacchi et al that analyzed PtM-AEL and PtM-PEM plants with CO 2 delivered from various point sources, the base-case values for PM and carcinogenic effects are higher than the results in Table S30 and S31 (see Supporting Information). Furthermore, the base-case value for freshwater eutrophication is lower, while the result for ionizing radiation is close to 2050’s results of PtM-AEL and PtM-PEM plants with air as the CO 2 source.…”
Section: Results and Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…In comparison to the study by Bargiacchi et al that analyzed PtM-AEL and PtM-PEM plants with CO 2 delivered from various point sources, the base-case values for PM and carcinogenic effects are higher than the results in Table S30 and S31 (see Supporting Information). Furthermore, the base-case value for freshwater eutrophication is lower, while the result for ionizing radiation is close to 2050’s results of PtM-AEL and PtM-PEM plants with air as the CO 2 source.…”
Section: Results and Discussioncontrasting
confidence: 70%
“…Moreover, the value published by Bargiacchi et al for the base-case scenario of PtM-AEL and PtM-PEM plants is approx. 6 kg CO 2 equiv/kg SNG using a FU of 1 kg of SNG and a scenario of the Italian energy mix in 2030 with a high share of NG (38.5%), PV (24.3%), hydro (16.1%), and wind (13.1%) power . The value is within the lower range of the results of PtM-AEL and PtM-PEM plants by applying the energy scenario in 2050 (see Figures –).…”
Section: Results and Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…We found that energy requirements for CO 2 capture and their associated emissions differ between specific CO 2 sources and capture processes, in line with M€ uller et al 128 and von der Assen et al 159 Whether a CCU process is Paris compatible can thus depend on the capture process itself (e.g., a DAC process based on natural gas 143 rather than renewable electricity 145 may render the entire CCU product non-Paris compatible). Our research has focused on available CO 2 source-CCU technology combinations in the LCA literature, and further research could harmonize CO 2 sources and capture processes to provide additional insights into remaining CO 2 source-CCU technology combinations.…”
Section: Sources Of Co 2 and Capture Processessupporting
confidence: 81%
“…These processes happen for remote consumers, so H 2 ESS is considered a clean technology [4]. (b) SNG: As natural gas has a lower sulphur and nitrogen content than coal and hydrocarbons, thus synthetic natural gas is a lower environmental impact than fuel because of the energy involved in the gas's creation [112].…”
Section: Chemical Energy Storage Systemsmentioning
confidence: 99%